Storax Protected Oxygen-Glucose Deprivation/Reoxygenation Induced Primary Astrocyte Injury by Inhibiting NF-κB Activation in vitro - Zhang, Meng; Ma, Yan; Chai, Lijuan; Mao, Haoping; Zhang, Junhua; Fan, Xiang (Frontiers in Pharmacology, 2019)
Stroke is the second leading cause of death and the leading cause of long-term disability in the world. There is an urgent unmet need to develop a range of neuroprotective strategies to restrain the damage that occurs in the hours and days following a stroke. Storax, a natural resin extracted from injuring Liquidambar orientalis Mill, has been used to treat acute stroke in traditional Chinese medicine for many centuries. Storax has demonstrated the neuroprotective effects in cerebrovascular diseases. However, the neuroprotective mechanisms activated by storax in ischemia/reperfusion-injured astrocytes have not been elucidated. In this study, we established an oxygen-glucose deprivation/reoxygenation (OGD/R)-induced astrocytes injury model to investigate the effects of storax on OGD/R-induced astrocytes injury and potential mechanisms. Experimental results showed that storax alleviated expression of inflammatory cytokines and protected primary cortical astrocytes injured by OGD/R. Furthermore, storax could inhibit NF-κB activation in injured astrocytes by OGD/R and inhibition of NF-κB with Bay-11-7082 obscured the neuroprotective effects of storax. In conclusion, storax alleviated expression of inflammatory cytokines and protected primary cortical astrocytes injured by OGD/R, which was partially mediated by NF-κB signaling pathway activation.